Coping in mexican adolescents with metabolic syndrome: a qualitative study - Onofre-Rodríguez, Dora Julia; CUEVA-LUNA, Teresa Elizabeth; Peláez-Ballestas, Ingris; Garza-Elizondo, María Eugenia; Benavides-Torres, Raquel Alicia (Acta Universitaria, 2019)
This paper describes the daily coping strategies among Mexican adolescents diagnosed with metabolic syndrome (MS). Data were collected through a semi-structured interview, using a phenomenology perspective. Nine adolescents diagnosed with MS aged 12-17 years were recruited from a public hospital in northeastern Mexico. Three thematic categories were obtained in the interview analysis: experiencing an MS diagnosis, adapting to health care and treatment, and decision-making to cope with the disease. Adolescents receiving an MS diagnosis were able to overcome their initial -often negative- experiences, they were motivated to adhere to management and treatment plans with support from health professionals, and they were able to develop adaptive coping strategies. Results indicate that, with support, adolescents could adapt to new prevention, management, and treatment strategies.